The Unsaid about British’s Withdraw from the European Union - BEDRE, Hadjira (My University, 2017)
After the Second World War, Britain was not far from becoming one part from the third world. The decline touched several fields from politics to economic and in many other sectors. People had lost their principal to continue alive. At the time, Britain tried hardly to find solutions and in 1973 it become one member of the EU. Britain contributed in many treaties of the Union during fourteen years and after this, Britain and after the general election left the Union. And after this the prime minister resigned for his position. The leave ring used the problems of immigrations as an convince arguments to win the war against the conservative government especially, with the support of Gove and Johnson, the two are MPS from the Tory party. and may be this explained the resignation of David Cameron. The immigration existed in Britain from a long time, and they served Britain and Britain’s economy, and this explained that the UKIP or the leave ring had another goal from their leaving the Union. Forage Nigel is an UKIP’s leader, who was believed in the Nationality like Margaret Thatcher, and they became alone as other nationalists after her death, but he won in making change in Britain. When he lead it out of the Union.
Keywords: Modern Britain; European Union's Withdraw; Causes and Impact; Modern history; Nationalists; Conservatives